A Re-examination of the Link between Real Exchange Rates and Real Interest Rate Differentials - Mathias Hoffmann; Ronald MacDonald (Center for Economic Studies and ifo Institute (CESifo), 2003)
The real exchange rate - real interest rate (RERI) relationship is central to most open economy macroeconomic models. However, empirical support for the relationship, especially when cointegrationbased methods are used, is rather weak. In this paper we reinvestigate the RERI relationship using bilateral real exchange rate data spanning the period 1978 to 1997. We first clarify the logic of applying cointegration methods to the RERI and propose an alternative way of testing the relationship. We demonstrate that the failure of earlier analyses to detect a stationary real interest rate is largely due to the low power of the tests employed.
Keywords: E43; F31; F41; 330; real exchange rates; real interest rates; cointegration